Options for Engineering Apomixis in Plants - Yin, Pei Pei; Tang, Li Ping; Zhang, Xian Sheng; Su, Ying Hua (Frontiers in Plant Science, 2022)
In plants, embryogenesis and reproduction are not strictly dependent on fertilization. Several species can produce embryos in seeds asexually, a process known as apomixis. Apomixis is defined as clonal asexual reproduction through seeds, whereby the progeny is identical to the maternal genotype, and provides valuable opportunities for developing superior cultivars, as its induction in agricultural crops can facilitate the development and maintenance of elite hybrid genotypes. In this review, we summarize the current understanding of apomixis and highlight the successful introduction of apomixis methods into sexual crops. In addition, we discuss the importance of understanding the mechanisms of somatic embryogenesis for parthenogenesis, a unique reproductive method of gametophytic apomixis. We also summarize three schemes to achieve engineered apomixis, which will offer more opportunities for the realization of apomictic reproduction.